H2S gas sensor film material for vacuum environment and preparation method of H2S gas sensor film material

By using SnO2-CuO or ZnO-CuO composite materials and ultraviolet light irradiation technology, the problem of degradation in the performance of traditional MOS sensors in vacuum environments is solved, and efficient H2S gas detection under vacuum conditions is achieved.

CN119595715AActive Publication Date: 2025-03-11HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411642292.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The performance of existing MOS sensors has significantly reduced their performance in vacuum or hypoxic environments, making it difficult to work effectively under extreme conditions such as deep space detection.

Method used

SnO2-CuO or ZnO-CuO composite material is used as the film material of the gas sensor. The reaction between CuO and H2S does not depend on oxygen, and it is combined with ultraviolet light to improve the reaction rate and sensitivity.

Benefits of technology

Achieve efficient H2S gas detection under vacuum conditions, which is suitable for application scenarios such as spacecraft and deep space exploration, and improves the sensitivity and response speed of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595715A_ABST
    Figure CN119595715A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas sensors, and provides an H2S gas sensor film material for a vacuum environment and a preparation method thereof, and the film material is a SnO2-CuO or ZnO-CuO composite material. According to the Cu ion doped SnO2-CuO and ZnO-CuO composite film prepared by the invention, the reaction of CuO and H2S does not depend on oxygen, and CuO can directly react with H2S to generate CuS, so that efficient H2S gas detection can be realized under a vacuum condition. By means of the mechanism, the sensor is particularly suitable for application scenes, such as spacecrafts and deep space exploration, where gas detection needs to be carried out under the low-oxygen or vacuum condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas sensors, and in particular to a H2S gas sensor thin film material for a vacuum environment and a preparation method thereof. Background Art

[0002] Existing gas sensors are mainly based on metal oxide semiconductor (MOS) materials and are widely used in environmental monitoring, industrial safety and health diagnosis. MOS sensors have excellent performance in H2S detection due to their simple structure, low cost and high sensitivity to gases.

[0003] However, most traditional MOS sensors rely on oxygen in the atmosphere for gas adsorption and reaction. Their performance in a vacuum or oxygen-deficient environment drops significantly, making it difficult for them to work effectively under extreme conditions such as deep space exploration. For example, when existing sensors detect H2S gas in a low-pressure environment, the detection sensitivity decreases as the oxygen content changes. These sensors mainly operate at room temperature, normal pressure or high temperature, rely on changes in surface adsorbed oxygen, and have a certain degree of recovery. In addition, the carrier concentration and electron mobility of metal oxide semiconductor materials decrease at low temperatures, resulting in a decrease in detection sensitivity. Therefore, there is an urgent need for an efficient gas sensor suitable for vacuum conditions. Summary of the invention

[0004] In view of this, the present invention proposes a thin film material for an efficient gas sensor suitable for vacuum conditions and a preparation method thereof.

[0005] The technical solution of the present invention is implemented as follows: In a first aspect, the present invention provides a H2S gas sensor thin film material for use in a vacuum environment, wherein the thin film material is a SnO2-CuO or ZnO-CuO composite material.

[0006] Traditional metal oxide gas sensors (such as pure SnO2 or ZnO) work well in atmospheric environments, mainly because gas adsorption and reaction rely on the participation of oxygen. Oxygen is adsorbed on the surface of the material to form adsorbed oxygen, which reacts with the target gas (such as H2S) to change the depletion layer thickness and form resistance changes. However, under vacuum or low oxygen content conditions, the surface adsorbed oxygen decreases as the vacuum increases, and its sensing performance will be seriously affected.

[0007] The Cu ion-doped SnO2-CuO and ZnO-CuO thin films prepared by the present invention do not rely on oxygen for the reaction between CuO and H2S. CuO can directly react with H2S to generate CuS, which can achieve efficient H2S gas detection under vacuum conditions. This mechanism makes the sensor particularly suitable for application scenarios such as spacecraft and deep space exploration that require gas detection under low oxygen or vacuum conditions.

[0008] On the basis of the above technical solution, preferably, the atomic ratio of Cu / Sn in the thin film material SnO2-CuO is 0.03-0.09:1, and the atomic ratio of Cu / Zn in the thin film material ZnO-CuO is 0.001-0.007:1.

[0009] In a second aspect, the present invention provides a method for preparing a H2S gas sensor thin film material for a vacuum environment, comprising the following steps:

[0010] S1, adding ethanol, water, zinc acetate or tin acetate into a reaction kettle and stirring them evenly as a basic solvent; then adding copper acetate and stirring the mixed solution until it is transparent and uniform;

[0011] S2, adding an alkaline reagent to adjust the pH of the mixed solution to 8-9, and then heating and stirring the mixed solution at 50-70° C. for 1-2 hours to form a sol;

[0012] S3, coating the sol on the substrate by spin coating technology, drying and calcining to obtain SnO2-CuO or ZnO-CuO thin film.

[0013] On the basis of the above technical solution, preferably, during the calcination in step S3, the substrate coated with the thin film is placed in an air atmosphere, kept at 400° C. to 600° C. for 1 to 2 hours, and then cooled.

[0014] On the basis of the above technical solution, preferably, in step S3, the coating rate is 2500-3000 rpm, the time is 20-30 s, and the thickness is 500-700 nm.

[0015] In a third aspect, the present invention provides an H2S gas sensor for use in a vacuum environment, wherein the sensor uses SnO2-CuO or ZnO-CuO thin film material as a gas sensitive material.

[0016] In a fourth aspect, the present invention provides a method for detecting H2S gas using a sensor, comprising the following steps:

[0017] S1, placing the sensor in a sealed cavity, wherein a UV-LED is arranged in the cavity, and the UV-LED irradiates the surface of the SnO2-CuO or ZnO-CuO film;

[0018] S2, the chamber is evacuated to 10 -3 Pa, and then inject H2S gas, and detect H2S gas under vacuum conditions.

[0019] UV irradiation provides additional energy to promote the reaction between CuO and H2S. This energy excitation can increase the reaction rate and the sensitivity of the sensor. Especially under vacuum conditions, the role of UV light is particularly important because it makes up for the lack of reaction kinetics caused by the lack of oxygen participation.

[0020] On the basis of the above technical solution, preferably, the wavelength band of the UV-LED is 360-365nm, and the power is 2600-2900mW.

[0021] On the basis of the above technical solution, preferably, the distance between the UV-LED and the thin film material is ≤5 cm.

[0022] The H2S gas sensor thin film material for vacuum environment and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0023] (1) In the SnO2-CuO and ZnO-CuO thin film materials prepared by the present invention, the reaction between CuO and H2S does not depend on oxygen, and can directly react to form CuS, so that the sensor can achieve efficient H2S gas detection under vacuum conditions. This mechanism makes the sensor particularly suitable for application scenarios such as spacecraft and deep space exploration that require gas detection under low oxygen or vacuum conditions.

[0024] (2) Under vacuum conditions, the sensor uses UV light to excite the carriers in SnO2-CuO and ZnO-CuO materials, increasing their surface energy states, thereby effectively improving the adsorption capacity of H2S gas and increasing the sensitivity of the sensor.

[0025] (3) The present invention uses SnO2-CuO and ZnO-CuO thin film materials as the gas-sensitive materials of the sensor, so that the sensor has a pn heterostructure, which can enhance the separation of electrons and holes, promote the efficient surface reaction, and thus improve the sensitivity, response speed and detection limit of the gas sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is the gas sensing performance test diagram of CuO-ZnO thin film gas sensor with different copper contents;

[0028] Figure 2 The response curve of the ZnO-CuO thin film sensor with a copper content of 0.7% when injected with different concentrations of H2S;

[0029] Figure 3SEM images of CuO-ZnO thin films, a is a low magnification SEM image, b is a high magnification SEM image, and c is a cross-sectional SEM image of the thin film;

[0030] Figure 4 is the EDS image of CuO-ZnO film, a is the EDS image of CuO-ZnO film, b is the EDS spectrum of CuO-ZnO film, c~e are the element distribution diagrams of O, Cu and Zn respectively;

[0031] Figure 5 This is the gas sensing performance test diagram of SnO2-CuO thin film gas sensor with different copper contents;

[0032] Figure 6 The response curve of SnO2-CuO thin film sensor with copper content of 9% injected with different concentrations of H2S;

[0033] Figure 7 SEM images of SnO2-CuO thin films, a is the front image, b is the cross-sectional image;

[0034] Figure 8 is the EDS image of SnO2-CuO film, a is the EDS image of CuO-SnO2 film, b is the EDS spectrum of CuO-SnO2 film, c~e correspond to the distribution of O, Cu, Sn elements in the film respectively;

[0035] Fig. 9 The response value curve of ZnO-CuO thin film gas sensor with copper content of 0.7% at different annealing temperatures to H2S;

[0036] Fig.10 The curves of the response resistance of SnO2-CuO thin film gas sensor with 9% copper content to H2S at different annealing temperatures are shown;

[0037] Fig.11 For 3×10 -3 Under the vacuum condition of Pa, the resistance change of SnO2-CuO and ZnO-CuO sensors under UV LED irradiation with time; a is the selectivity of SnO2-CuO and ZnO-CuO sensors to different gases (CO, NO2, H2, H2S) at 10ppm, b is the change of sensor sensitivity with H2S concentration (0-25ppm), and c is the detection limit of the sensor;

[0038] Fig.12 PL photoluminescence spectra of pure ZnO and CuO-ZnO thin films;

[0039] Fig.13 PL photoluminescence spectra of pure SnO2 and SnO2-CuO films;

[0040] Fig.14 For display in 3×10 -3 Under Pa vacuum conditions, the resistance variation of SnO2-CuO (Figure a) and ZnO-CuO (Figure b) sensors in the dark and under UV (365nm) LED irradiation over time;

[0041] Fig.15 This is the internal structure diagram of the sensor;

[0042] Fig.16 This is a performance comparison chart of Ag2O-SnO2 and SnO2-CuO. DETAILED DESCRIPTION

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The present invention provides a gas sensor for detecting H2S gas in a vacuum environment. The gas sensor uses SnO2-CuO and ZnO-CuO thin films as gas sensitive materials. The gas sensor of the present invention is different from the existing gas sensor in that an ultraviolet lamp is provided inside the cavity for irradiating the SnO2-CuO and ZnO-CuO thin films, and the distance between the ultraviolet lamp and the SnO2-CuO and ZnO-CuO thin film materials is ≤5 cm (see Fig.15 ).

[0045] As shown in the figure, the gas sensor of the present invention is located in a closed cavity, and a mechanical pump / molecular pump, a source meter, an ionization gauge / resistance gauge and a gas injection device are provided on the top of the cavity. The gas injection device is used to inject the H2S gas to be detected; the mechanical pump / molecular pump is a vacuum pumping device, used to extract the air in the cavity to keep it in a vacuum state; the ionization gauge / resistance gauge is used to detect the vacuum degree in the cavity, the resistance gauge is used to detect low vacuum, and the ionization gauge is used to detect high vacuum; the source meter provides power support for the gas sensor and the ultraviolet lamp.

[0046] Example 1

[0047] The preparation method of the ZnO-CuO thin film material for the H2S gas sensor in a vacuum environment in this embodiment is as follows:

[0048] S1, add 0.01 mol zinc acetate (Zn(CH3COO)2·2H2O) into 50 mL ethanol aqueous solution with a volume concentration of 75% prepared from anhydrous ethanol and deionized water, heat and stir at 75°C to dissolve it as a basic solvent for later use.

[0049] S2, adding copper acetate (Cu(CH3COO)2·H2O) to the solution of step S1 according to a set doping ratio of Cu / Zn atomic ratio (molar ratio) of 0.001 to 0.009:1, and stirring the mixed solution until it becomes transparent to obtain a precursor solution.

[0050] S3, to improve stability, alkaline agent sodium hydroxide (NaOH) was added to the precursor solution to adjust the pH value of the solution to 8. Then, the solution was heated and stirred at 60°C for 1 h to form a uniform sol.

[0051] S4, the prepared sol is coated on the substrate (interdigitated electrode) by spin coating technology, the spin coating rate is set to 3000 rpm, the duration is 20 seconds, and the thickness is 645 nm.

[0052] S5, after coating, the substrate (interdigitated electrodes) is placed in an oven, dried at 100° C. for 30 minutes to remove the solvent, and then calcined at 450° C. for 2 hours to obtain a ZnO-CuO thin film.

[0053] ZnO-CuO films doped with different Cu contents were used as gas-sensitive materials for gas sensors. Gas sensors were prepared and gas detection experiments were carried out to evaluate their response performance in H2S gas.

[0054] The detection method is as follows: a ZnO-CuO thin film gas sensor is placed in a sealed cavity, a UV-LED is arranged in the cavity, the distance between the UV-LED and the thin film material is ≤5cm, and the UV-LED irradiates the surface of the ZnO-CuO thin film, the UV-LED has a wavelength of 360nm and a power of 2900mW; the cavity is evacuated to 10 -3 Pa, and then inject H2S gas, and detect H2S gas under vacuum conditions.

[0055] pass Figure 1 By analyzing the curve, it can be concluded that the response values ​​of the ZnO-CuO thin film gas sensor to 7.5ppm H2S are 2.63, 3.86, 5.96, 7.51 and 11.63 respectively. When the copper content does not exceed 0.7%, the response value increases with the increase of copper content; when the copper content increases from 0.7% (atomic ratio of 0.007:1) to 0.9% (atomic ratio of 0.007:1), the response value decreases slightly. This shows that when the copper content in the film is 0.7%, the sensitivity of the sensor to H2S reaches the highest. This may be because as the copper content increases, the number of heterojunctions in the film also increases, thereby preventing the resistance value of the sensor from further decreasing.

[0056] Figure 2The response of the ZnO-CuO thin film gas sensor with a copper content of 0.7% was measured as a function of H2S gas concentration. The test method was as follows: -3 Pa) and UV (360nm) irradiation conditions. As shown in the figure, the sensor's response values ​​to 2.5ppm, 5ppm, 10ppm, 15ppm, 20ppm, and 25ppm H2S gas are 5.03, 8.02, 15.05, 21.03, 28.18, and 45.75, respectively. It can be concluded that the sensor's response value increases with the increase of H2S concentration.

[0057] The microstructure, main element composition and ratio of ZnO-CuO composite films were characterized by field emission scanning electron microscopy (SEM). Figure 3 As shown. Figure (a) shows the front image of the ZnO-CuO nanofilm magnified 27,000 times, and it can be seen that the surface of the film is relatively rough. After further magnification to 112,000 times, it can be clearly observed that the film is composed of nanoparticles. The morphology of the nanoparticles is relatively uniform, and the average particle size is between 30-50nm, as shown in Figure (b). In order to observe the approximate thickness of the film, a cross-sectional image of the CuO-ZnO film was taken as shown in Figure (c), and it can be clearly seen that the thickness of the film is about 645nm.

[0058] Figure 4 The EDS images of ZnO-CuO thin films are shown. Figures (c-e) show that the three elements O, Cu, and Zn are evenly distributed in the film. The EDS spectrum in Figure (b) can be used to check the elemental composition and ratio of the film. The elemental ratio of Cu to Zn is 0.48 / 54.88=0.0087, which is roughly consistent with the calibrated ratio of 0.009.

[0059] Example 2

[0060] The preparation method of SnO2-CuO thin film material for H2S gas sensor in vacuum environment of this embodiment is as follows:

[0061] S1, add 0.01 mol of tin acetate (Sn(CH3COO)2) into 50 mL of 75% ethanol aqueous solution prepared from anhydrous ethanol and deionized water, heat and stir at 75°C to dissolve it as a base solvent for later use.

[0062] S2, adding copper acetate (Cu(CH3COO)2·H2O) to the solution of step S1 according to a set doping ratio of Cu / Sn atomic ratio (molar ratio) of 0.03 to 0.12:1, and stirring the mixed solution until it becomes transparent to obtain a precursor solution.

[0063] S3, to improve stability, alkaline agent monoethanolamine (C2H7NO) was added to the precursor solution to adjust the pH value of the solution to 9. Then, the solution was heated and stirred at 70°C for 1 h to form a uniform sol.

[0064] S4, the prepared sol is coated on a substrate such as glass or silicon wafer by spin coating technology, the spin coating rate is set to 2000 rpm, the duration is 30 seconds, and the thickness is 640 nm.

[0065] S5, after coating, the substrate is placed in an oven and dried at 100° C. for 30 minutes to remove the solvent, and then calcined at 450° C. for 2 hours to obtain a SnO2-CuO film.

[0066] SnO2-CuO films doped with different Cu contents were used as gas-sensitive materials for gas sensors. Gas sensors were prepared and gas detection experiments were carried out to evaluate their response performance in H2S gas.

[0067] The detection method is as follows: the SnO2-CuO sensor is placed in a sealed cavity, a UV-LED is arranged in the cavity, the distance between the UV-LED and the film material is ≤5cm, and the UV-LED irradiates the surface of the SnO2-CuO film, the UV-LED has a wavelength of 365nm and a power of 2600mW; the cavity is evacuated to 10 -3 Pa, and then inject H2S gas, and detect H2S gas under vacuum conditions.

[0068] Figure 5 It can be seen that the pure SnO2 sensor is almost insensitive to H2S, while the response values ​​of the sensors with copper contents of 3%, 6%, 9% and 12% to 15ppm H2S are 39, 623, 2403 and 2268 respectively. Similarly, the response value of the sensor increases with the increase of copper content. However, when the Cu content increases from 9% to 12%, the response value of the sensor does not continue to increase, but decreases slightly. This is because after reacting with the injected H2S gas, there are still many heterojunctions in the SnO2-CuO film, which limits the further reduction of the sensor's resistance. In other words, with the increase of copper content, the sensitivity of the sensor shows a trend of first increasing and then decreasing. When the copper content is 9%, the sensitivity of the sensor to H2S reaches the highest.

[0069] Figure 6 The SnO2-CuO thin film gas sensor with 9% copper content was studied at room temperature (25℃) and vacuum (10 -3The gas-sensing performance of H2S gas of different concentrations under irradiation of 1ppm (0.3767 W) and ultraviolet light (365nm) is plotted as a response value-time curve. As shown in the figure, after injecting H2S gas of different concentrations, the sensor also shows different degrees of response values. The sensor response values ​​corresponding to the injection of 1ppm, 2ppm, 5ppm, 15ppm, and 25ppm H2S gas are 83.2, 117.4, 650, 2469, and 9799, respectively, which shows that the response value of the sensor increases with the increase of H2S concentration.

[0070] The microstructure and elemental composition of SnO2-CuO thin films were observed by field emission scanning electron microscopy (SEM). Figure 7 Image (a) is a front image of the SnO2-CuO film magnified 100,000 times, showing that the film is composed of many tightly stacked small nanoparticles, including small particles with diameters between 10-20nm and some larger particles with diameters between 30-50nm. Image (b) shows a cross-sectional view of the SnO2-CuO film, from which it can be seen that the thickness of the film is about 0.64μm.

[0071] Figure 8 The EDS image of SnO2-CuO film doped with 0.09 copper content is shown. The information in the EDS spectrum in Figure (b) can be used to check the elemental composition and proportion of the film. By calculation, the atomic ratio of Cu and Sn elements is 2.47 / 25.01=0.098, which is consistent with the nominal proportion of Cu in the heterojunction film (9%). Figures (c-e) show the uniform distribution of O, Cu, and Sn in the film.

[0072] Test 1 The effect of different heat treatment temperatures on the sensor

[0073] Calcination temperature affects the growth of CuO grains. The higher the temperature, the more CuO is formed, which is more conducive to the reaction with H2S, which is consistent with the design idea. However, the higher the heating temperature is, the better the response effect is not necessarily the case. Different proportions and temperatures have an impact on performance. Taking the 0.7% ZnO-CuO film prepared in Example 1 and the 9% SnO2-CuO film prepared in Example 2 as examples, the gas-sensing properties of the films were tested at different heat treatment temperatures (450°C, 500°C, 550°C and 600°C), and the results are shown in Table 1. Fig. 9 and 10 .

[0074] By calculation, it can be concluded that the response values ​​of the gas sensor to 18ppm H2S gas are 2.7, 4.04, 26.6 and 12.1 respectively for 0.7% ZnO-CuO films calcined at 450℃, 500℃, 550℃ and 600℃ (see Fig. 9). It shows that the response value of the sensor with heat treatment temperature of 450℃ and 500℃ is lower, and the slope of the response curve is also lower, which means that the response speed is slow. The slope of the response curve of the sensor calcined at 550℃ and 600℃ is higher, and the response speed is faster. By comparison, it can be seen that the response value of the sensor at 550℃ is higher than that of the sensor at 600℃, indicating that the sensor prepared at this temperature has a higher sensitivity to H2S.

[0075] By calculation, it can be concluded that the response values ​​of the gas sensor to 5ppm H2S gas are 16.5, 41.6, 638 and 478 for 9% SnO2-CuO films calcined at 450℃, 500℃, 550℃ and 600℃ respectively (see Fig.10 ). By observing the response curve, it can be found that the sensors heat-treated at 450℃ and 500℃ show lower response values ​​and slower response speeds. In contrast, the gas sensors calcined at 550℃ and 600℃ have higher response values ​​and curve slopes. Further comparison shows that the response value of the sensor at 550℃ is higher than that of the sensor at 600℃, indicating that the sensor heat-treated at this temperature has the highest sensitivity to H2S.

[0076] Test the detection sensitivity of the second sensor

[0077] Taking the 0.7% ZnO-CuO2 thin film gas sensor prepared in Example 1 and the 9% SnO2-CuO thin film gas sensor prepared in Example 2 as examples, the detection -3 The selectivity of SnO2-CuO and ZnO-CuO sensors to different gases (CO, NO2, H2, H2S) at 10 ppm under vacuum conditions is shown in Fig.11 .

[0078] As shown in Figure a, the SnO2-CuO and ZnO-CuO thin film gas sensors of the present invention can detect not only H2S, but also CO, NO2 and H2 gases, with greater selectivity. As shown in Figure b, with the increase of H2S concentration (0-25ppm), the response of SnO2-CuO and ZnO-CuO sensors to H2S is also getting higher and higher, which further indicates that the sensitivity of the sensors is good; as shown in Figure c, the detection limit of SnO2-CuO and ZnO-CuO sensors is 100ppb H2S.

[0079] Comparative Example 1

[0080] Comparative Example 1 uses a pure ZnO film, and no copper acetate is added during the preparation of the ZnO film. The rest of the contents are the same as in Example 1.

[0081] The photoinduced carrier separation efficiency of CuO / ZnO thin films was studied by PL photospectroscopy. The principle of PL photospectroscopy is to irradiate light of a specific wavelength onto the sample to excite electrons in the valence band to transition to the conduction band, thereby forming electron-hole pairs. After a certain period of time, the excited electrons will return to the valence band and recombine with holes. The recombination process will release photons and emit fluorescence. The fluorescence intensity of photons of different wavelengths can be measured by a spectrometer to obtain the photoinduced spectrum.

[0082] The PL photospectroscopy of pure ZnO film and CuO-ZnO film with a copper content of 0.7% was tested at 365nm. Fig.12 shown.

[0083] Fig.12 It shows that pure ZnO film has higher fluorescence intensity than 0.7% CuO-ZnO film, which indicates that as the copper content of the film increases, the number of heterojunctions in the film also increases. Since the heterojunction can effectively separate photogenerated carriers and inhibit their recombination, this leads to lower fluorescence intensity.

[0084] Comparative Example 2

[0085] Comparative Example 2 uses pure SnO2 film, and no copper acetate is added during the preparation of the SnO2 film. The rest of the contents are the same as Example 2.

[0086] PL photoluminescence spectra of pure SnO2 film and 9% SnO2-CuO film at 365nm. Fig.13 It can be observed that the pure SnO2 film has a higher PL intensity than the SnO2-CuO film, which means that the recombination rate of photogenerated electrons and holes is higher. With the introduction of CuO, the PL intensity of the film is significantly reduced, indicating that the recombination of photogenerated carriers is suppressed, which is attributed to the ability of the heterojunction formed in the film to efficiently separate photogenerated carriers. Photogenerated electrons and holes are separated into different regions of the heterojunction. These phenomena indicate the formation of the SnO2-CuO heterojunction.

[0087] Comparative Example 3

[0088] The sensors prepared with the 0.7% ZnO-CuO film prepared in Example 1 and the 9% SnO2-CuO film prepared in Example 2 as gas sensitive materials were used to detect H2S gas under UV irradiation (365nm) and in the dark without UV irradiation. The results are shown in FIG. Fig.14 .

[0089] Fig.14As shown in a and b, UV irradiation significantly improves the gas adsorption capacity and electron mobility on the surface of ZnO-CuO and SnO2-CuO materials, shortening the response time of ZnO-CuO and SnO2-CuO thin film gas sensors to H2S gas, thereby improving the detection accuracy.

[0090] Comparative Example 4

[0091] Comparative Example 4 is compared with Example 2, except that Ag2O replaces CuO to prepare 9% Ag2O-SnO2, and the rest of the contents are the same. The results are shown in Fig.16 .

[0092] Composite nanoparticles containing the same proportion (9%) of Ag2O were synthesized and reacted with 10 ppm H2S under light conditions. The reacted materials were then placed in air and heated at 100°C for 24 h, and then measured and compared again.

[0093] Fig.16 It can be seen that the stability of Ag2O-SnO2 composite nanoparticles gradually decreases with time and finally loses its activity, while the performance of CuO composite materials remains basically unchanged, indicating that CuO has better stability than Ag2O.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A H2S gas sensor thin film material for vacuum environment, characterized in that: The film material is a SnO2-CuO or ZnO-CuO composite material.

2. The H2S gas sensor thin film material for vacuum environment according to claim 1, characterized in that: The atomic ratio of Cu / Sn in the thin film material SnO2-CuO is 0.03-0.09:1, and the atomic ratio of Cu / Zn in the thin film material ZnO-CuO is 0.001-0.007:

1.

3. A method for preparing a H2S gas sensor thin film material for a vacuum environment as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1, adding ethanol, water, zinc acetate or tin acetate into a reaction kettle and stirring them evenly as a basic solvent; then adding copper acetate and stirring the mixed solution until it is transparent and uniform; S2, adding an alkaline reagent to adjust the pH of the mixed solution to 8-9, and then heating and stirring the mixed solution at 50-70° C. for 1-2 hours to form a sol; S3, coating the sol on the substrate by spin coating technology, drying and calcining to obtain SnO2-CuO or ZnO-CuO thin film.

4. The method for preparing a H2S gas sensor thin film material for a vacuum environment as claimed in claim 3, characterized in that: During the calcination in step S3, the substrate coated with the thin film is placed in an air atmosphere, kept at 400° C. to 600° C. for 1 to 2 hours, and then cooled.

5. The method for preparing a H2S gas sensor thin film material for a vacuum environment as claimed in claim 3, characterized in that: In step S3, the coating rate is 2500-3000 rpm and the time is 20-30 s.

6. The method for preparing a H2S gas sensor thin film material for a vacuum environment as claimed in claim 3, characterized in that: The coating thickness in step S3 is 500-700 nm.

7. A H2S gas sensor for use in a vacuum environment, characterized in that: The sensor uses the SnO2-CuO or ZnO-CuO thin film material described in claim 1 or 2 as a gas-sensitive material.

8. A method for detecting H2S gas using the sensor according to claim 7, characterized in that: The following steps are involved: S1, placing the sensor in a sealed cavity, wherein a UV-LED is arranged in the cavity, and the UV-LED irradiates the surface of the SnO2-CuO or ZnO-CuO film; S2, the chamber is evacuated to 10 -3 Pa, and then inject H2S gas, and detect H2S gas under vacuum conditions.

9. The method for detecting H2S gas by a sensor as claimed in claim 8, characterized in that: The wavelength of the UV-LED is 360-365nm, and the power is 2600-2900mW.

10. The method for detecting H2S gas by using a sensor as claimed in claim 8, characterized in that: The distance between UV-LED and film material is ≤5cm.

Citation Information

Patent Citations

  • Hydrogen sulfide gas concentration detection device and detection method based on ultraviolet catalytic conversion

    CN109490237A

  • Composite material for detecting H2S gas in lunar soil volatile components and preparation method thereof

    CN115974138A

  • Composite material for detecting H2S gas at low temperature as well as preparation and application of composite material

    CN116332226A

  • Room temperature UV-activated hydrogen gas sensor

    US20210190721A1

  • Ultraviolet toxic gas point detector

    US5936250A